Effects of long-term loading on fire-damaged reinforced-concrete stub columns. Issue 9 (23rd March 2018) - Huo, Jingsi; Liu, Hanqing; Xu, Xi
Abstract : The effect of long-term loading on fire-damaged reinforced-concrete (RC) stub columns was experimentally investigated. RC stub columns were axially loaded and heated to predetermined temperatures. After the specimens were cooled to ambient temperature, long-term loading was applied and kept constant for 98 d and 192 d and axial deformations due to the creep effect were recorded. The specimens were then compressed to failure. The residual compressive strength and residual compression stiffness were analysed to assess the effect of long-term loading on the post-fire mechanical behaviour of the specimens. It was found that long-term loading had a significant effect on the residual mechanical behaviour of fire-damaged RC stub columns. The fire-damaged specimens resulted in obviously increased creep during the loading period. Based on the model given in ACI 209R-92 and existing experimental data on fire-damaged concrete obtained previously by the authors, a fire-induced creep modification factor is proposed to predict the creep of fire-damaged concrete under long-term loading. It is recommended that the effect of creep should be taken into consideration in assessing fire-damaged RC columns.